The Russian Orthodox Church and Moscow-the Third Rome Concept - Ş. Muhammed Duali (Milel ve Nihal)

(untitled)
In 988, under the leadership of Kinyaz Viladimer, Russians accepted Christianity through the Patriarchate of Constantinople and entered a new phase in their history. With Christianity, the Russians were introduced to writing and, most importantly, to religious texts. At the same time, this religious conversion also led to the acceptance of the belief of chosenness, which had spread to Christianity from Judaism. Nestor, a Russian priest who lived in the 12th century, wrote in his work that although Russians were the last community to accept Christianity, they would undertake important missions in the future. He also attributed a mission to the Russian society by referring to the biblical passage that the feet will be the head and the head will be the feet. However, in the mentioned centuries, the Eastern Roman Empire was still the center of Orthodoxy. For this reason, the Russian Orthodox Church would remain for many years as a Metropolitanate under the Patriarchate of Constantinople. However, the increasing Ottoman pressure on Constantinople from the 1400s onwards created several historical opportunities for the Russians. In particular, the Byzantine agreement with the Pope of Rome in Florence in 1439 mobilized the Russian Church. Using this agreement as a pretext, Moscow severed its relations with Constantinople. In 1453, the Ottoman conquest of Constantinople, the center of the Orthodox world, opened a new page in Russian Theo-politics. Russian priests believed that Nestor's prophecy had been fulfilled and Moscow developed the concept of the Third Rome. Appearing in the 16th century, the Moscow-Third Rome concept soon became the ideological basis for the formation of the Moscow kingdom. In this article, the concept of Moscow Third Rome, which is one of the important turning points in Russian history, is analyzed through an analytical method. The background of the concept, the conditions that led to its emergence, its historical development and its reflections on the present day are emphasized.